Analysis of Auditory Brainstem Response test time using Narrow Band Level Specific CE-Chirp and Tone Burst in Infants: ABR and Test time - Bin Dzulkarnain, Ahmad Aidil; Mohamad Noor, Amnah; Jamaluddin, Saiful Adli Jamaluddin; Rahmat, Sarah; Mohd Zain, Siti Rashidah (International Journal of Allied Health Sciences, 2025)
Background and Aims: Despite advancements in auditory brainstem response (ABR) stimuli, the clinical application of narrow-band level-specific CE-Chirp (NB LS CE-Chirp) and the objective F-test multiple points (Fmp) algorithm remains underexplored, particularly in infant populations. These methodologies hold promise for improving the efficiency of ABR assessments and universal newborn hearing screening. This study evaluates the use of NB LS CE-Chirp as a test stimulus and the Fmp statistical algorithm as a stopping criterion to address prolonged ABR test durations. Subjects and Methods: Fifty infants (27 males, 23 females) under six months of age were enrolled. ABR recordings were obtained using both NB LS CE-Chirp and tone burst (TB) stimuli at 500, 1000, and 4000 Hz, presented at 70 and 40 dBnHL. Test durations were calculated using two stopping criteria: Fmp ? 3.1 and visual detection. Results: NB LS CE-Chirp stimuli elicited significantly shorter test durations across all frequency and intensity combinations compared to TB stimuli, under both Fmp ? 3.1 and visual detection criteria. Notably, the Fmp ? 3.1 algorithm did not consistently yield shorter test times than visual detection for either stimulus type. Conclusion: The use of NB LS CE-Chirp stimuli, combined with either visual or Fmp-based detection algorithms, presents a promising strategy for infant hearing assessment. This approach significantly reduces ABR test duration and may enhance the efficiency of newborn hearing screening protocols.